2020
DOI: 10.1038/s41598-020-69801-6
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction mechanism of Paramisgurnus dabryanus loach with self-lubricating and flexible micro-morphology

Abstract: Underwater machinery withstands great resistance in the water, which can result in consumption of a large amount of power. inspired by the character that loach could move quickly in mud, the drag reduction mechanism of Paramisgurnus dabryanus loach is discussed in this paper. Subjected to the compression and scraping of water and sediments, a loach could not only secrete a lubricating mucus film, but also importantly, retain its mucus well from losing rapidly through its surface micro structure. In addition, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…It can be concluded that the drag force gradually increases with the increase of fluid velocity. According to eqn (4) , 26 the drag reduction rate of the bionic surface can be calculated. where η is drag reduction rate, F ts is the resistance of the smooth surface, F tb is the resistance of the bionic surface.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that the drag force gradually increases with the increase of fluid velocity. According to eqn (4) , 26 the drag reduction rate of the bionic surface can be calculated. where η is drag reduction rate, F ts is the resistance of the smooth surface, F tb is the resistance of the bionic surface.…”
Section: Resultsmentioning
confidence: 99%
“…This could be because vortexes are formed around the bionic fish scale so that the high‐speed flow fluid was far from the near‐wall region. Therefore, the sudden increase in the turbulence was greatly weakened, and the drag‐reduction effect was obtained (Bai, Zhang, Song, Boyce, & Ortiz, 2016; Wu et al, 2020). Figure 9c shows the velocity magnitude of the bionic dual‐composite surface, in which the outer layer covers the flexible epidermis layer of the tuna and the inner surface comprises hard scales.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the drag reduction of loach surface structure, the flexible deformation mode of loach body also contributes to further increase the drag reduction rate. Loach, due to its self-adaptive characteristics, can always keep the drag reduction rate at a high level within a wide speed range [ 107 ], and the maximum drag reduction capacity can even reach 33.63% [ 108 ].…”
Section: Synergistic Drag Reduction Analysis Of Mucus-groovementioning
confidence: 99%
“… Microscopic morphology of loach body: (a) loach, (b) scale morphology, (c) different positions on the same scale, (d) groove structure, and (e) groove cross section [ 107 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation